Empowering Health Workers to Build Public Trust in Vaccination: Experience from the International Pediatric Association's Online Vaccine Trust Course, 2020–2021. Issue 2 (9th January 2023) - Uttekar, Shraddha; MacDonald, Noni; Orenstein, Walter A; Danchin, Margie; Blaser, Vince; Thomson, Angus; Menning, Lisa; Shimp, Lora; Rath, Barbara; Limaye, Rupali; Esangbedo, Dorothy; Abeyesekera, Surangani; et al.
Abstract: Background: The quality of interactions between health workers (HWs) and caregivers is key in vaccine acceptance. To optimize this, HWs need knowledge about best vaccine communication practices in person and on social media. Most pre-service curricula do not include such approaches. COVID-19 necessitated the International Pediatric Association (IPA) to shift from in-person train the trainer workshops to developing an online Vaccine Trust Course to address these gaps. Method: The seven-module, 8-hour Vaccine Trust Course was offered online in seven languages and promoted globally. Course outcomes for participants between September 1, 2020 and September 30, 2021 were assessed using enrollment, participation, and completion data; pre-and post-training surveys of attitudes, knowledge, and practice skills; and follow-up practice surveys 3 months post course completion. Results: Of the 4, 926 participants across 137 countries who registered; 2, 381 (48.3 %) started the course, with 1, 217 (51.1 %) completing. The majority were 25 – 39 years (57 %), female (57 %), and in pediatrics (70 %); 31 % came from India. 62 % of completers rated course structure/design as excellent, 36 % as good. Over 80 % rated the content as the most valuable aspect. Three months post training, 61 % HWs reported increased empathy towards caregivers, confidence while counseling and increased vaccine acceptance amongst their patients. 21 % identified the course as the only factor in these positive changes. Conclusion: Shifting from face-to-face to online training due to the COVID-19 pandemic helped increase the global reach of HWs course engagement and uptake. Trained HWs reported increased empathy towards caregivers and confidence while counseling and increased patient vaccine acceptance.